INTAKE OF MINANG CULTURAL VALUES AS STRENGTHENING THE CHARACTER OF THE NATION'S CHILDREN IN SHORT STORIES “TSUNAMI” BY ISMALINAR - Syahrul, Ninawati; Sunarti, Sastri; Atisah, Atisah; Fadlly, Harits (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2024)
This research will analyze the cultural values and local wisdom of the Minang ethnic group contained in the short story